Systematic Literature Riview: Peningkatan Hasil Belajar Matematika Melalui Model Teams Games Tournament - Nuri Ria Sri Wahyuni; Rhomiy Handican (Pendidikan Matematika FKIP Universitas Mataram, 2023)
In learning, innovation is needed that can attract students' interest in learning mathematics, one of which is by using the Teams Games Tournament method that can improve student learning outcomes. This study aims to conduct a literature review on the use of team game tournaments to improve students' mathematics learning outcomes. The research method chosen in this study is the SLR (Systematic Literature Review) method. Data collection used with the review is all articles regarding the use of the Teams Games Tournament method published in the period 2013-2022. The articles used in this study were 15 accredited National journal articles obtained from the Google Scholar database. Based on this research, it was found that the use of the Teams Games Tournament method could improve student learning outcomes.